Female fighters : why rebel groups recruit women for war - Wood, Reed (Reed M.) (Columbia University Press, 2019)
"The presence of women combatants on the battlefield--especially in large numbers--strikes many observers as a notable departure from the historical norm. Yet women have played significant active roles in many contemporary armed rebellions. Over recent decades, numerous resistance movements in many regions of the globe have deployed thousands of female fighters in combat. Reed M. Wood explains why some rebel groups deploy women in combat while others exclude women from their ranks, and the strategic implication of this decision. Examining a vast original dataset on female fighters in over 250 rebel organizations, Wood argues rebel groups can gain considerable strategic advances by including women fighters. Drawing on women increases the pool of available recruits and helps ameliorate resource constraints. The visible presence of female fighters often becomes an important propaganda tool for domestic and international audiences. Images of women combatants help raise a group's visibility, boost local recruitment, and aid the group's efforts to solicit support from transnational actors and diaspora communities. However, Wood finds that, regardless of the wartime resource challenges they face, religious fundamentalist rebels consistently resist utilizing female fighters. A rich, data-driven study, Female Fighters presents a systematic, comprehensive analysis of the impact women's participation has on organized political violence in the modern era"--